The association between body image and depressive symptoms in pregnant and postpartum women: a meta-analysis - He, Jingbo; Chen, Xin; Luo, Biru (Frontiers in Public Health, 2025)
BackgroundBody image is an individual’s internal representation of physical appearance. Perinatal depression, a psychological condition with severe implications, is influenced by body dissatisfaction. However, no studies have systematically quantified their association.ObjectiveTo evaluate the correlation between body image and depressive symptoms in the perinatal period through meta-analysis.MethodsA systematic search was conducted in PubMed, Embase, The Cochrane Library, Medline, CNKI, Wanfang, and VIP databases, and studies assessing body image and perinatal depression were included. Two researchers independently screened, extracted, and assessed study quality. Meta-analysis used Review Manager 5.4, with the correlation coefficient (r) as the effect size, and studies assessing body image and perinatal depression were included.ResultsTwenty-eight studies involving 7,241 women were included. For pregnancy, the summary r for the reverse and forward scoring groups was 0.34 (95% CI: 0.24, 0.44; p < 0.01) and −0.34 (95% CI: −0.37, −0.30; p < 0.01), respectively. The four dimensions of body image (Feeling Fat, Attractiveness, Salience of Weight and Shape, and Strength and Fitness) were 0.34 (95% CI: 0.28, 0.40), −0.36 (95% CI: −0.42, −0.31), 0.31 (95% CI: 0.25, 0.36), and −0.32 (95% CI: −0.37, −0.26), respectively (all p < 0.01). For postpartum, the summary r = 0.35 (95% CI: 0.26, 0.43; p < 0.01) (reverse scoring group), and for the four dimensions: 0.30 (95% CI: 0.23, 0.38), −0.41 (95% CI: −0.46, −0.36), 0.27 (95% CI: 0.20, 0.35), and −0.34 (95% CI: −0.39, −0.28), respectively (all p < 0.01). The results for all subgroups were robust, with no significant publication bias.ConclusionBody dissatisfaction is consistently and moderately associated with perinatal depression. Early identification and interventions may help prevent depression and improve maternal–infant health outcomes.Systematic review registrationPROSPERO, identifier CRD42025639158, https://www.crd.york.ac.uk/PROSPERO/view/CRD42025639158.